The lives of the great composers - Schonberg, Harold C. 1915-2003 (Norton, 1997)
This updated and expanded edition of the perennial favorite traces the line of composers from Monteverde to the tonalists of the 1990s. Schonberg discusses the lives and works of the foremost figures in classical music, weaving a fabric rich in detail and anecdote. Photos.